2016
DOI: 10.4067/s0718-16202016000200011
|View full text |Cite
|
Sign up to set email alerts
|

NUTRITIONAL AND FUNCTIONAL CHARACTERIZATION OF WILD AND CULTIVATED Sarcocornia neei GROWN IN CHILE

Abstract: Sarcocornia neei is a halophyte that grows on the coast of the Valparaiso Region of Chile. Studies related to its nutritional and functional value under wild and cultivated conditions are not available. Thus, in this study, a nutritional (complete proximal, mineral and dietary fiber analysis) and functional characterization (total phenolics, β-carotene, hydrophilic and lipophilic antioxidant activity (HAA and LAA) and ascorbic acid) were performed for wild and cultivated plants. Wild plants displayed higher am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 29 publications
3
23
0
6
Order By: Relevance
“…Nitrogen bioaccumulation was not determined empirically in this study, but we derived it from Riquelme et al [22], a previous study performed by our research group. Riquelme et al [22] show that the total of N fixed in the aerial part of S. neei corresponds to 1.76 ± 0.08 g per 100 g of fresh weight. Similar results were obtained in S. brachiata by Rathore et al [39] from India.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen bioaccumulation was not determined empirically in this study, but we derived it from Riquelme et al [22], a previous study performed by our research group. Riquelme et al [22] show that the total of N fixed in the aerial part of S. neei corresponds to 1.76 ± 0.08 g per 100 g of fresh weight. Similar results were obtained in S. brachiata by Rathore et al [39] from India.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some species of the genus Spartina show a higher affinity for NH 4 + consumption [18,19], while others like Juncus maritimus, have a marked preference for NO 3 -, even in substrates that contained high availability of NH 4 + [20]. Also, if the plants are grown in lysimeters or wetland, the interaction with soil, microorganism and plant have a higher potential to remove nitrogen compounds and produce biomass, which can be used as animal feed or human food [21,22], and in the production of biofuels or by-products of interest to the pharmaceutical industry [2,5,15,23,24], among others. Additionally, it has been demonstrated that these systems are also efficient in removing residual phosphates from RASs [2,15,23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein content in Selliera radicans is within this range and comparable to vegetables consumed daily. 11,[40][41][42] Macro and micronutrients contents of halophytes depend on several factors, such as the plant species, stage of growth, season, and others. [41][42] Content of macro and micronutrients in cultivated Selliera radicans leaves are in Table 2 and all these values are lower than cultivated S. neei.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…11,[40][41][42] Macro and micronutrients contents of halophytes depend on several factors, such as the plant species, stage of growth, season, and others. [41][42] Content of macro and micronutrients in cultivated Selliera radicans leaves are in Table 2 and all these values are lower than cultivated S. neei. 41 For instance, in 100 g of fresh S. neei plants collected in coastal marsh and irrigated with sea water there were 8.07 g of Na, 41 while in S. radicans there were only 0.66 g of Na, irrigated with tap water containing 17 mg L -1 sodium.…”
Section: Discussion/conclusionmentioning
confidence: 99%